The Enlightenment and Guidance of the Theory of Qi, Blood, Phlegm, and Stagnation for Modern Emotional Disorders Treatment - Cheng, Zhiru (International Journal of Public Health and Medical Research, 2024)
Zhu Danxi’s emotional disorder theory, as an important part of traditional Chinese medicine, reveals the etiology and treatment methods of emotional disorders through core concepts such as the "Theory of Qi, Blood, Phlegm, and Stagnation," and the "Theory of Ministerial Fire." This paper explores the application of Zhu Danxi’s theories, such as the Yin-Nourishing Theory, Six Stagnations Theory, and Emotion Regulating Method, in comparison with modern emotional disorder therapies such as cognitive therapy and Morita therapy. Research shows that Zhu’s theory not only has unique advantages in regulating emotions and balancing the mind and body but also provides innovative ideas for modern mental disorder treatment, emphasizing dialectical treatment and emotional regulation. On this basis, the paper proposes combining Zhu Danxi’s theories with modern treatment methods to create a more personalized and comprehensive emotional disorder treatment system to improve clinical efficacy and patient quality of life. This paper aims to promote the integration of traditional Chinese emotional disorder theories with modern psychology and provide new theoretical foundations and practical guidance for Chinese medicine psychology.